A new record and cuticular structure of Meyeria magna (Decapoda, Mecochiridae) from the lower Albian (Lower Cretaceous) of Colombia. (January 2016) - González-León, Oscar; Patarroyo, Pedro; Moreno-Bedmar, Josep Anton; Nyborg, Torrey; Vega, Francisco J.
Abstract: Eleven specimens of the lobster Meyeria magna from the Simití Formation (Santander Province, Colombia) represent a new occurrence for this species in South America. Ammonites collected both below and above the bed that yielded M . magna allow dating of these specimens as early Albian. Morphological characteristics observed in these Colombian specimens were compared with those of other specimens from Mexico, the United Kingdom and Spain. Our interpretation of the cuticular structure in thin section does not unambiguously allow interpretation of the specimens studied to corpses or molts. Highlights: Taxonomic description of the 11 decapods crustacean specimen of Meyeria magna species from the Simití Formation, Vélez Área in the Santander province, Colombia. We analyze for the first time the cuticular structure in Meyeria magna from Colombia, Mexico, UK and Spain. The analysis of the cuticular structure in Meyeria magna allows differentiating between corpses and molts.